THE INFLUENCE OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEES’ PERFORMANCE - Faadillah, Maulana Rizky; Noermijati, Noermijati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the effect of the work environment and work motivation on the performance of employees at the sub-district office of Malang City, specifically in the Lowokwaru Subdistrict, Blimbing Subdistrict, Klojen Subdistrict, Sukun Subdistrict, and Kedungkandang Subdistrict. This research is explanatory research and employs quantitative methods. The study involved a sample of 103 respondents selected through the census method. The criteria for respondents included active employees of the sub-district office of Malang City. The questionnaire items were rated using a Likert scale, with scores ranging from 1 to 5. The research employed the Statistical Package for the Social Sciences (SPSS) for conducting validity tests, reliability tests, and classical assumption tests. The data analysis methods used in this study was the multiple linear regression test. The results of the hypothesis testing show that the data related to the work environment (X1) significantly affects employee performance, whereas work motivation (X2) does not have a significant effect on employee performance.